JS waterproof coating prepared from waste building materials and straw through resource utilization and preparation method of JS waterproof coating
JS waterproof coating, which is made by recycling waste building materials and straw resources, solves the problem of improper disposal of construction waste, achieves improved environmental, economic and social benefits, and has excellent coating performance.
Patent Information
- Application Number
- CN202511066643.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-09-26
AI Technical Summary
If construction waste is not properly handled, it will lead to waste of land resources, damage to hydrogeological structures, pollution of the environment, impact on social aesthetics and economic burden. The existing extensive landfill treatment method is insufficient.
JS waterproof coating, which uses waste building materials and straw resources, consists of component A and component B. Component A includes acrylic emulsion, enhancer, etc., and component B includes cement, construction waste processed materials and straw processed materials, etc. They are prepared by mixing in a specific proportion to form a high-performance waterproof coating.
It has achieved the goal of reducing landfill pressure, reducing pollution, lowering construction costs, and promoting the development of green buildings. The coating performance meets national standards and the waterproof membrane has good stability.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of environmental science and engineering, and in particular to a JS waterproof coating for resource utilization of waste building materials and straw and a preparation method thereof. Background Art
[0002] The common extensive landfill disposal method for construction solid waste not only wastes land resources but also damages the regional hydrogeological structure. Therefore, resource utilization of construction solid waste is of great significance in reducing land resource waste, creating recycled value, and improving environmental protection.
[0003] Polymer cement waterproof coating (JS waterproof coating for short) is a two-component water-based building waterproofing material composed of an organic high-molecular polymer emulsion and an inorganic cement-based material. Polymer cement waterproof coating is formulated with polymer emulsions such as acrylates and ethylene-vinyl acetate (VAE) and cement as its primary raw materials. It is also formulated with cement (Silicate or ordinary Portland cement), quartz sand, ground calcium carbonate filler, and other additives. It cures through water evaporation and chemical reactions to form a film, creating a flexible and rigid waterproof layer.
[0004] Epoxy resin waterproof coating is a high-performance waterproof material with epoxy resin as its primary film-forming substance. Formulated with curing agents, diluents, fillers, and other additives, it is widely used in construction, underground engineering, water conservancy facilities, and other fields. Its core characteristics lie in its strong chemical stability, excellent adhesion, and high mechanical strength. It forms a dense waterproof layer that effectively blocks water penetration.
[0005] If not properly handled, construction waste can cause serious harm to the environment, society, and the economy. From an environmental perspective, the indiscriminate storage of large amounts of construction waste consumes valuable land resources, destroys soil structure, reduces soil fertility, and hinders vegetation growth. Harmful substances such as heavy metals and chemical additives can be washed into the ground by rainwater, contaminating soil and groundwater, threatening the balance and stability of ecosystems and potentially harming human health through the food chain. During storage and transportation, dust generated by construction waste exacerbates air pollution, reduces air quality, and harms human respiratory health. Socially, the disorderly storage of construction waste degrades the aesthetics of cities, disrupts their appearance, and reduces residents' quality of life. The resulting environmental problems can also lead to resident dissatisfaction. Economically, handling construction waste requires significant human, material, and financial resources, placing an increased financial burden on governments and businesses. Without resource utilization, large quantities of recyclable and reusable building materials are wasted, resulting in resource depletion and undermining sustainable development. Summary of the Invention
[0006] In order to overcome the shortcomings of the common extensive landfill treatment method of construction solid waste in the existing technology, which not only leads to waste of land resources but also destroys the regional hydrogeological structure, the present invention provides a JS waterproof coating for resource utilization of waste building materials and straw and a preparation method thereof, which solves the problem that construction waste is not properly treated and causes serious harm to the environment, society and economy.
[0007] To achieve the aforementioned object of the invention, the technical solutions adopted by the present invention include:
[0008] A JS waterproof coating for recycling waste building materials and straw, comprising a component A and a component B, wherein the mass ratio of the component A to the component B is 1:(1-3);
[0009] Component A and component B respectively include the following raw materials in the following mass proportions:
[0010] Component A: 90-94 parts of acrylic emulsion, 4.5-8.5 parts of water, 0.5 parts of enhancer, 0.2-0.3 parts of defoamer, 0.2-0.3 parts of antifreeze, 0.1-0.2 parts of matting agent, 0.1-0.2 parts of thickener, and 0.1-0.2 parts of preservative;
[0011] Component B: 35-50 parts of cement, 15-30 parts of treated construction waste, 9.8-14.9 parts of quartz sand, 10-15 parts of epoxy resin emulsion, 5-15 parts of treated straw, and 0.1-0.2 parts of curing agent.
[0012] In the component A, the reinforcing agent is aluminum silicate, the defoaming agent is silicone oil, the antifreeze agent is selected from at least one of ethylene glycol, propylene glycol, and ethanol, the matting agent is silicon dioxide, the thickener is selected from at least one of carboxymethyl cellulose and methyl cellulose, and the preservative is selected from at least one of sodium benzoate, potassium sorbate, and benzoic acid.
[0013] The curing agent in the B component is selected from at least one of polyethylene polyamine, ethylene triamine, and diethylaminopropylamine.
[0014] The preparation method of the JS waterproof coating by resource utilization of waste building materials and straw comprises the following steps:
[0015] Step 1: Preparation of component A
[0016] 1-1) Place acrylic emulsion into a reactor, add water and antifreeze, and then stir at 600-800 rpm for 10-20 minutes while controlling the temperature at 30-50°C to fully mix the components.
[0017] 1-2) Grind and sieve the reinforcing agent, matting agent, and preservative to a particle size of less than 200 mesh, and add them to the mixed solution obtained in step 1-1), controlling the temperature to 50-60°C and stirring at 1000-1200 rpm for 30 minutes;
[0018] 1-3) adding a thickener to the mixed solution obtained in step 1-2) to adjust the viscosity to 3000-5000 mPa·s;
[0019] Step 2: Preparation of component B
[0020] 2-1) Construction waste processing: waste bricks, waste cement, waste slate and other waste materials are crushed, ground and sieved to make the particle size less than 200 mesh;
[0021] 2-2) Preparation of processed straw: Crush the straw, grind it, and sieve it to a particle size of less than 200 mesh. Then soak it in 1-2 mol / L potassium hydroxide solution at 50-60°C for 3 hours. Then filter and separate the straw particles and dry them at 40-60°C to constant weight.
[0022] 2-3) Add cement, treated construction waste, quartz sand, treated straw, epoxy resin emulsion, and curing agent into the reactor and stir at 600-800 rpm for 10-20 minutes at 40-60°C;
[0023] Step 3: Mix components A and B in a mass ratio of 1: (1-3) and use.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present application provides a JS waterproof coating for resource utilization of waste building materials and straw and a preparation method thereof. In terms of environmental benefits, it reduces landfill pressure and pollution; in terms of economic benefits, it reduces construction costs and transportation costs; in terms of social benefits, it promotes the development of green buildings.
[0026] The production process of the process of this application is safe and simple, with low cost. The performance of the waterproof coating obtained by this method meets national standards, the film formation is stable, and it has good waterproof performance. Half a year after the coating is applied, the waterproof film is still stable and impermeable, and has good stability. DETAILED DESCRIPTION
[0027] The following examples are illustrative descriptions of the primary experimental evidence and are not intended to limit the core content and application scope of the present invention to the amount of evidence. If the chain of evidence is complete, it is not necessary to present all the specific details and extended details of each example listed in the present invention.
[0028] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.
[0029] Example 1
[0030] Step 1: The materials of component A are mixed in proportions by mass: 90 parts of acrylic emulsion, 8.5 parts of water, 0.5 parts of aluminum silicate, 0.25 parts of silicone oil, 0.25 parts of ethylene glycol, 0.2 parts of silicon dioxide, 0.2 parts of methyl cellulose, and 0.1 parts of sodium benzoate.
[0031] Acrylic emulsion, water, and ethylene glycol were placed in a reactor and stirred at 800 rpm for 15 minutes to obtain mixed solution 1. The reinforcing agent, matting agent, and preservative were then ground through a 200-mesh sieve to obtain pharmaceutical granules. The resulting pharmaceutical granules were then added to mixed solution 1. The temperature was controlled at 50°C and stirred at 1000 rpm for 30 minutes. Finally, a binder was added to adjust the viscosity to 4000 mPa·s. This yielded component A.
[0032] Step 2: Prepare the following Component B materials by weight: 50 parts cement, 15 parts treated construction waste, 14.9 parts quartz sand, 15 parts epoxy resin emulsion, 5 parts treated straw, and 0.1 part polyethylene polyamine. Crush, grind, and sieve waste bricks, waste cement, and waste slabs to obtain treated construction waste with a particle size of less than 200 mesh. Crush, grind, and sieve straw to obtain straw pellets with a particle size of less than 200 mesh. Soak the straw pellets in 1 mol / L potassium hydroxide solution at 60°C for 3 hours. Then, filter and separate the straw pellets and dry them at 40°C to a constant weight. Add cement, treated construction waste, quartz sand, treated straw, epoxy resin emulsion, and polyethylene polyamine to a reactor and stir at 50°C and 600 rpm for 20 minutes. This yields Component B.
[0033] Step 3: Mix component A and component B in a mass ratio of 1:1.
[0034] Example 2
[0035] Step 1: Mix the materials of component A in proportion by mass: 94 parts of acrylic emulsion, 4.5 parts of water, 0.5 parts of aluminum silicate, 0.3 parts of silicone oil, 0.3 parts of ethylene glycol, 0.1 parts of silicon dioxide, 0.2 parts of carboxymethyl cellulose, and 0.1 parts of sodium benzoate.
[0036] Acrylic emulsion, water, and ethylene glycol were placed in a reactor and stirred at 800 rpm for 15 minutes to obtain Mixture 1. The enhancer, matting agent, and preservative were then ground through a 200-mesh sieve to obtain pharmaceutical granules. The resulting pharmaceutical granules were then added to Mixture 1. The mixture was stirred at 1200 rpm and controlled at 60°C for 30 minutes. Finally, a binder was added to adjust the viscosity to 5000 mPa·s to obtain Component A.
[0037] Step 2: Prepare the following Component B materials by weight: 40 parts cement, 25 parts treated construction waste, 14.8 parts quartz sand, 10 parts epoxy resin emulsion, 10 parts treated straw, and 0.2 parts polyethylene polyamine. Crush, grind, and sieve waste materials such as waste bricks, waste cement, and waste slabs to obtain treated construction waste with a particle size of less than 200 mesh. Crush, grind, and sieve straw to obtain straw pellets with a particle size of less than 200 mesh. Soak the straw pellets in 1 mol / L potassium hydroxide solution at 60°C for 3 hours. Then, filter and separate the straw pellets and dry them at 60°C to a constant weight. Add cement, treated construction waste, quartz sand, treated straw, epoxy resin emulsion, and polyethylene polyamine to a reactor and stir at 800 rpm at 40°C for 10 minutes. This yields Component B.
[0038] Step 3: Mix component A and component B in a mass ratio of 1:2.
[0039] Example 3
[0040] Step 1: The materials of component A are mixed in proportions by mass: 92 parts of acrylic emulsion, 6.5 parts of water, 0.5 parts of aluminum silicate, 0.2 parts of silicone oil, 0.2 parts of ethanol, 0.2 parts of silicon dioxide, 0.2 parts of methyl cellulose, and 0.2 parts of benzoic acid.
[0041] Acrylic emulsion, water, and ethanol were placed in a reactor and stirred at 700 rpm for 15 minutes to obtain Mixture 1. The enhancer, matting agent, and preservative were then ground through a 200-mesh sieve to obtain pharmaceutical granules. The resulting pharmaceutical granules were then added to Mixture 1. The mixture was stirred at 1200 rpm and controlled at 60°C for 30 minutes. Finally, a binder was added to adjust the viscosity to 4500 mPa·s to obtain Component A.
[0042] Step 2: Prepare the following Component B materials by weight: 40 parts cement, 25 parts treated construction waste, 14.9 parts quartz sand, 10 parts epoxy resin emulsion, 10 parts treated straw, and 0.1 parts diethylaminopropylamine. Crush, grind, and sieve waste bricks, waste cement, and waste slabs to obtain treated construction waste with a particle size of less than 200 mesh. Crush, grind, and sieve straw to obtain straw pellets with a particle size of less than 200 mesh. Soak the straw pellets in 1 mol / L potassium hydroxide solution at 60°C for 3 hours. Then, filter and separate the straw pellets and dry them at 60°C to a constant weight. Add cement, treated construction waste, quartz sand, treated straw, epoxy resin emulsion, and diethylaminopropylamine to a reactor and stir at 800 rpm at 60°C for 10 minutes to obtain Component B.
[0043] Step 3: Mix component A and component B in a mass ratio of 1:1.
[0044] Example 4
[0045] Step 1: Component A materials are mixed in proportions by mass: 91 parts of acrylic emulsion, 7.5 parts of water, 0.5 parts of aluminum silicate, 0.3 parts of silicone oil, 0.25 parts of propylene glycol, 0.15 parts of silicon dioxide, 0.1 parts of carboxymethyl cellulose, and 0.2 parts of potassium sorbate.
[0046] Acrylic emulsion, water, and propylene glycol were placed in a reactor and stirred at 600 rpm for 15 minutes to obtain Mixture 1. The enhancer, matting agent, and preservative were then ground through a 200-mesh sieve to obtain pharmaceutical granules. The resulting pharmaceutical granules were then added to Mixture 1. The mixture was stirred at 1000 rpm and controlled at 60°C for 30 minutes. Finally, a binder was added to adjust the viscosity to 3000 mPa·s to obtain Component A.
[0047] Step 2: Prepare the following Component B materials by weight: 35 parts cement, 30 parts treated construction waste, 9.8 parts quartz sand, 10 parts epoxy resin emulsion, 15 parts treated straw, and 0.2 parts ethylenetriamine. Crush, grind, and sieve waste bricks, waste cement, and waste slabs to obtain treated construction waste with a particle size of less than 200 mesh. Crush, grind, and sieve straw to obtain straw pellets with a particle size of less than 200 mesh. Soak the straw pellets in a 2 mol / L potassium hydroxide solution at 50°C for 3 hours. Then, filter and separate the straw pellets and dry them at 60°C to a constant weight. Add cement, treated construction waste, quartz sand, treated straw, epoxy resin emulsion, and ethylenetriamine to a reactor and stir at 60°C and 700 rpm for 15 minutes. This yields Component B.
[0048] Step 3: Mix component A and component B in a mass ratio of 1:3.
[0049] Performance Tests of Various Embodiments
[0050] According to the test methods of GB / T 23445-2009 for tensile properties (untreated), elongation at break (untreated), bonding strength (untreated), impermeability (back side of mortar), and water impermeability (0.3 MPa, 30 min), application examples 1-4 were tested for untreated tensile properties (>=1.8 MPa), untreated elongation at break (>=80%), untreated bonding strength (>=0.7 MPa), impermeability (>=0.6 MPa), and water impermeability.
[0051] The experimental results are shown in the following table:
[0052] Untreated tensile strength (MPa) Untreated elongation at break (%) Untreated bonding strength (MPa) Impermeability (mortar back water surface) Water impermeability (0.3MPa, 30min) Application Example 1 2.45 228 0.8 0.7 impermeable Application Example 2 3.33 208 1.1 0.9 impermeable Application Example 3 2.05 235 1.0 0.8 impermeable Application Example 4 3.09 203 0.9 0.8 impermeable
[0053] The experimental results show that the physical and mechanical properties of the product meet the Type II technical indicators.
[0054] It should be understood that the above embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. For those skilled in the art of the present invention, without departing from the concept of the present invention, several changes or substitutions can be made, which should be considered to fall within the scope of protection of the present invention.
Claims
1. A JS waterproof coating for recycling waste building materials and straw, characterized in that: It is composed of component A and component B, and the mass ratio of component A to component B is 1: (1-3); Component A and component B respectively include the following raw materials in the following mass proportions: Component A: 90-94 parts of acrylic emulsion, 4.5-8.5 parts of water, 0.5 parts of enhancer, 0.2-0.3 parts of defoamer, 0.2-0.3 parts of antifreeze, 0.1-0.2 parts of matting agent, 0.1-0.2 parts of thickener, and 0.1-0.2 parts of preservative; Component B: 35-50 parts of cement, 15-30 parts of treated construction waste, 9.8-14.9 parts of quartz sand, 10-15 parts of epoxy resin emulsion, 5-15 parts of treated straw, and 0.1-0.2 parts of curing agent.
2. The JS waterproof coating for recycling waste building materials and straw according to claim 1, characterized in that: In the component A, the reinforcing agent is aluminum silicate, the defoaming agent is silicone oil, the antifreeze agent is selected from at least one of ethylene glycol, propylene glycol, and ethanol, the matting agent is silicon dioxide, the thickener is selected from at least one of carboxymethyl cellulose and methyl cellulose, and the preservative is selected from at least one of sodium benzoate, potassium sorbate, and benzoic acid.
3. The JS waterproof coating for recycling waste building materials and straw according to claim 1, characterized in that: The curing agent in the B component is selected from at least one of polyethylene polyamine, ethylene triamine, and diethylaminopropylamine.
4. The method for preparing a JS waterproof coating for recycling waste building materials and straw according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Preparation of component A 1-1) Place acrylic emulsion into a reactor, add water and antifreeze, and then stir at 600-800 rpm for 10-20 minutes while controlling the temperature at 30-50°C to fully mix the components. 1-2) Grind and sieve the reinforcing agent, matting agent, and preservative to a particle size of less than 200 mesh, and add them to the mixed solution obtained in step 1-1), controlling the temperature to 50-60°C and stirring at 1000-1200 rpm for 30 minutes; 1-3) adding a thickener to the mixed solution obtained in step 1-2) to adjust the viscosity to 3000-5000 mPa·s; Step 2: Preparation of component B 2-1) Construction waste processing: waste bricks, waste cement, waste slate and other waste materials are crushed, ground and sieved to make the particle size less than 200 mesh; 2-2) Preparation of processed straw: Crush the straw, grind it, and sieve it to a particle size of less than 200 mesh. Then soak it in 1-2 mol / L potassium hydroxide solution at 50-60°C for 3 hours. Then filter and separate the straw particles and dry them at 40-60°C to constant weight. 2-3) Add cement, treated construction waste, quartz sand, treated straw, epoxy resin emulsion, and curing agent into the reactor and stir at 600-800 rpm for 10-20 minutes at 40-60°C; Step 3: Mix components A and B in a mass ratio of 1: (1-3) and use.